The formation of social capital in Malay traditional settlement - Hassan, Nur 'Adilah; Harun, Nor Zalina; Abdullah, Alias (Malaysian Institute Of Planners, 2020)
Good practices of traditional settlement’s preservation allow all actors to engage and explore what makes a self-sustaining settlement by the locals. This study aims to identify the values of social capital that have influenced the social capital sustainability in Malay traditional settlement. For this purpose, semi-structured interview and non-participant observation were performed on Pulau Duyong, Terengganu as the selected Malay traditional settlement. The findings from this study revealed that the sustainability of social capital in the study area was achieved through a well-planned development with the involvement of the community, non-governmental organizations and authority as well as the integration and collective actions among the actors. The contribution of this study resides in the capacity to provide a useful guide for future social capital sustainability developments in a place with high heritage values.